CanSat design and implementation for remote sensing applications - Atallah, Mohammed; Alkalbani, Dhabiya; Alsheryani, Maha; Albedwawi, Moza; Alshehhi, Reem; Almeqbaali, Reem; Okasha, Mohamed; Dief, Tarek N. (Applied Research and Smart Technology (ARSTech), 2022)
With the increasing potential of satellite technology, it becomes crucial to learn its principles and develop the basic satellite subsystems for the undergraduate level. Working on a real satellite is a challenging target and requires a solid technical background. In contrast, less complex models, such as CanSat, CubSat and HeptaSat, introduce basic ideas to the undergraduate studies level. This paper presents the CanSat design and implementation for remote sensing applications such as measuring the CO2 level in contaminated areas. The CanSat has the size of a soft drink can and simulates the subsystems of the satellite (e.g., payload, power, communication, onboard computer, and structural). Its mission was to be released from a certain altitude and send real-time data to the ground station during landing. The design process was elucidated at the subsystem level. It included the mission requirements and specifications, component selection, and software and hardware design. Arduino Nano was utilised as an onboard computer. A printed Circuit Board (PCB) was designed using Diptrace© to connect the electronic components to Arduino Nano. Xbee was used as a communication module to send the collected data to the host computer. This data was visualised in real-time by LabView©.